FAMILY OWNERSHIP MATTERS FOR INVESTORS IN INDONESIA'S MINING COMPANIES - Purnamawati, I Gusti Ayu; Yuniarta, Gede Adi; Suwena, Kadek Rai; Heryanda, Komang Krisna; Hatane, Saarce Elyse (Petra Christian University, 2023)
This study aims to determine the effect of family ownership, financial performance, return on assets, return on equity, liquidity, and capital structure on market value. Secondary data was obtained based on annual reports and financial statements in mining companies listed on the IDX in 2016-2020 through Indonesia Stock Exchange (IDX). Data were obtained from the Bloomberg database. The method used to collect samples is purposive and consists of 35 mining companies in Indonesia. The panel data method was considered appropriate in this study, and multiple regression was used to examine the data. The results show that total assets and return on assets positively affect market value. The ratio of return on equity and liquidity in financial performance and capital structure has no significant effect on market value. The existence of family ownership is favourable for a firm’s market value. The sample in this study was limited to the manufacturing sector. This industry was chosen because its market value is quite volatile and family ownership is quite large. On average there are 40% of the total observations are family-owned companies. The interesting findings in this study are that family ownership does matter in gaining the investors’ attention.